Effect of Hot Isostatic Pressing and Rare-Earth Elements Addition on the Microstructure and Hardness on Inconel 718 - Medrano Prieto, Hansel M.; Castro Carmona, Javier Servando; Camacho Montes, Hector; Garay Reyes, C. G.; Ruiz-Esparza-Rodríguez, M. A.; Estrada Guel, Ivanovich; Guía Tello, J. C.; Rodríguez Cabriales, G.; Santos Beltran, A.; Martínez Sanchez, Roberto (2021)
Inconel 718 superalloy is highly employed in high-temperature applications; its principal properties are high resistance to oxidation and excellent mechanical performance. Such alloys are generally used in aeronautics and aerospace engines, power generation, and the chemical industry. Recent studies on the influence of rare-earth elements as rhenium, hafnium, tantalum, niobium, and ruthenium have enlarged to develop superalloys with higher microstructural properties and mechanical performance. Also, significant effects on microstructural and mechanical properties because of cerium and yttrium additions have been reported due to an increase in the lattice mismatch and the grain boundaries, furthermore, promotes modifications in carbides and eutectic phases.